Calcium contacts to n‐type crystalline silicon solar cells. (17th November 2016) - Allen, Thomas G.; Bullock, James; Zheng, Peiting; Vaughan, Ben; Barr, Matthew; Wan, Yimao; Samundsett, Christian; Walter, Daniel; Javey, Ali; Cuevas, Andres
Abstract: Direct metallization of lightly doped n‐type crystalline silicon (c‐Si) is known to routinely produce non‐Ohmic (rectifying) contact behaviour. This has inhibited the development of n‐type c‐Si solar cells with partial rear contacts, an increasingly popular cell design for high performance p‐type c‐Si solar cells. In this contribution we demonstrate that low resistance Ohmic contact to n‐type c‐Si wafers can be achieved by incorporating a thin layer of the low work function metal calcium (ϕ ~2.9 eV) between the silicon surface and an overlying aluminium capping layer. Using this approach, contact resistivities of ρ c  ~ 2 mΩcm 2 can be realised on undiffused n‐type silicon, thus enabling partial rear contacts cell designs on n‐type silicon without the need for a phosphorus diffusion. Integrating the Ca/Al stack into a partial rear contact solar cell architecture fabricated on a lightly doped ( N D  = 4.5 × 10 14  cm −3 ) n‐type wafer resulted in a device efficiency of η  = 17.6% where the Ca/Al contact comprised only ~1.26% of the rear surface. We demonstrate an improvement in this cell structure to an efficiency of η  = 20.3% by simply increasing the wafer doping by an order of magnitude to N D  = 5.4 × 10 15  cm −3 . Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We demonstrate that low resistance Ohmic contact to n‐type crystalline silicon wafers can be achieved by incorporating a thin layer of calcium between the silicon surface and an overlying aluminium capping layer. Integrating the Ca/Al stack into an n‐type partial rear contact solar cell architecture resulted in a device efficiency of η  = 20.3% where the Ca/Al contact comprised only ~1.26% of the rear surface. This is the first demonstration of an n‐type partial rear contacts cell with the direct metallization of the rear contacts without the use of phosphorus diffusion.